High-Temperature Crystal Chemistry of Meta-Autunite Group Minerals: Metatorbernite, Cu(UO2)2(PO4)2(H2O)8 and Metazeunerite, Cu(UO2)2(AsO4)2(H2O)8 - Evgeny V. Nazarchuk; Vladislav V. Gurzhiy; Yana G. Tagirova; Dmitri O. Charkin; Maria G. Krzhizhanovskaya; Anatoly V. Kasatkin; Oleg V. Eremin (Crystals, 2023)
Thermal expansion of metatorbernite, Cu(UO2)2(PO4)2(H2O)8 (1), and metazeunerite, Cu(UO2)2(AsO4)2(H2O)8 (2), has been investigated using single-crystal and powder X-ray diffraction. Both minerals are prone to dehydration, which proceeds already at ambient conditions. According to the single-crystal XRD data, 1 is stable up to 300(50) K, while 2 is stable up to 250(50) K. Powder XRD studies at various temperatures suggest that 1 dehydrates in three stages at ca. 353, 373, and 483 K, while 2 in two stages at ca. 283 and 543 K. Calculation of the main coefficients of thermal expansion reveals strong anisotropy. The expansion is maximal in the direction normal to the autunite-type layers. This correlates with the anisotropy in thermal evolution of Cu–O bond lengths and differences in the thermal behavior of PO4 and AsO4 tetrahedra.